Characterization of the Ld-restricted cytotoxic T-lymphocyte epitope in the mouse hepatitis virus nucleocapsid protein. - Bergmann, C (1993)
The mouse hepatitis virus (MHV) JHM strain (JHMV) produces primary demyelination in the central nervous system associated with acute encephalomyelitis. Humoral and cellular immune responses both participate in controlling the development of chronic MHV-induced demyelination. A subset of the CD8+ cytotoxic T lymphocytes (CTL) induced by immunization of BALB/c (H-2d) mice with JHMV is specific for the viral nucleocapsid protein. This CTL population recognizes an epitope located within the carboxy-terminal 149 amino acids in association with the Ld class I molecule (S. A. Stohlman, S. Kyuwa, M. Cohen, C. Bergmann, J. P. Polo, J. Yeh, R. Anthony, and J. G. Keck, Virology 189:217-224, 1992). Using a panel of vaccinia virus recombinants expressing truncated forms of the nucleocapsid protein and a series of overlapping synthetic peptides, we mapped the response to 15 amino acids. This sequence, encompassing the MHV epitope, contains the Ld-specific binding motif. The predicted 9-mer peptide (residues 318 to 326: APTAGAFFF) was sufficient and highly active in sensitizing target cells for CTL recognition when either added exogenously or synthesized intracellularly. Cross-reactivity of JHMV nucleocapsid protein-specific CTL with six other MHV strains indicated that natural sequence variations within the 9-mer epitope are tolerated in positions 4 and 5, whereas all other amino acids are conserved. These data define a novel 9-mer Ld-restricted CTL epitope which represents the first MHV CTL epitope. Characterization of this epitope provides a molecular basis to study the role of nucleocapsid protein-specific CTL in the clearance of JHMV from the central nervous system.